Estudo do processo de colagem de materiais dissimilares - Silveira, Thaís Almeida (Universidade Federal de São Carlos, 2023)
An examination of current literature aimed to investigate aspects relevant to the bonding of dissimilar materials, using as a scenario the joining of materials present in a multinational manufacturer of residential stoves and ovens. The industrial process uses glass, steel and glass fiber-reinforced polyamide 66 composite as adherends, and silicone as adhesive. The hypotheses analyzed were the thickness of the adhesive, the surface treatments of the polymeric adherend and the behavior of silicone as an adhesive. The thickness of the adhesive influences the adhesion power; but it is not well described by any analytical formula analytical formula and its optimum value must be determined experimentally. Plasma is an excellent pre-bonding treatment for preparing the surface of polymers, improving adhesion power. This can be optimized if combined with mechanical treatments aimed at increasing surface roughness. Silicone has excellent adhesion power, cures with air humidity and is able to adapt to the environmental conditions to which the final product will be exposed, such as humidity, UV radiation and thermal cycles.
Study of the bonding process of dissimilar materials
Keywords: Colagem; Adesivo; Tratamentos superficiais; Plasma; Espessura do adesivo; Rugosidade; Silicone; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS